'In any case, you believe him one hundred percent, everything he says.' Trustworthiness in Holocaust survivor talks with high school students in Germany. Issue 2 (3rd April 2022) - Ballis, Anja; Schwendemann, Lisa
ABSTRACT: Our study will turn to one Jewish male Holocuast survivor who visited ten high schools in Germany from January to March 2020. Based on the results of empirical and theoretical considerations of testifying, a communicative model was considered appropriate for understanding the encounter. Of special concern was to what extent trustworthiness was constructed during these talks by students. A mixed methods approach was chosen, combining testimony analysis with empirical tools in social science. The result of the study points to the students' trust in the survivor story, which is supported by the school institution and by the survivor's narration, his rhetorical strategies, and his personality.